Advanced Cataloging of Lysine-63 Polyubiquitin Networks by Genomic, Interactome, and Sensor-Based Proteomic Analyses. Issue 1 (11th November 2019) - Romero-Barrios, Natali; Monachello, Dario; Dolde, Ulla; Wong, Aloysius; San Clemente, Hélène; Cayrel, Anne; Johnson, Alexander; Lurin, Claire; Vert, Grégory
Abstract : Comprehensive analysis of Lys-63 polyubiquitination sheds light on its importance to plant growth and development and identifies the machinery driving this posttranslational modification. Abstract: The lack of resolution when studying the many different ubiquitin chain types found in eukaryotic cells has been a major hurdle to our understanding of their specific roles. We currently have very little insight into the cellular and physiological functions of Lys-63 (K63)–linked ubiquitin chains, although they are the second most abundant forms of ubiquitin in plant cells. To overcome this problem, we developed several large-scale approaches to characterize (1) the E2-E3 ubiquitination machinery driving K63-linked ubiquitin chain formation and (2) K63 polyubiquitination targets to provide a comprehensive picture of K63 polyubiquitin networks in Arabidopsis ( Arabidopsis thaliana ). Our work identified the ubiquitin-conjugating enzymes (E2s) UBC35/36 as the major drivers of K63 polyubiquitin chain formation and highlights the major role of these proteins in plant growth and development. Interactome approaches allowed us to identify many proteins that interact with the K63 polyubiquitination-dedicated E2s UBC35/36 and their cognate E2 variants, including more than a dozen E3 ligases and their putative targets. In parallel, we improved the in vivo detection of proteins decorated with K63-linked ubiquitin chains by sensor-based proteomics, yielding important insights into the roles of K63 polyubiquitination in plant cells. This work strongly increases our understanding of K63 polyubiquitination networks and functions in plants.